The association of medical, social, and normative factors with the implementation of end-of-life care practices - Arnona Ziv; Adir Shaulov; Carmit Rubin; Bernice Oberman; Yoel Tawil; Giora Kaplan; Baruch Velan; Moran Bodas (BMC, 2024)
Abstract Background End-of-life (EoL) care practices (EoLCP) are procedures carried out at the EoL and bear directly on this stage in the patient's life. Public support of these practices in Israel is far from uniform. Previous studies show that while ∼30% of participants support artificial respiration or feeding of terminally ill patients, 66% support analgesic treatment, even at the risk of shortening life. This study aimed to create a typology of six end-of-life care practices in Israel and assess the association of medical, social, and normative factors with the implementation of those practices. These practices included mechanical ventilation, artificial feeding, deep sedation, providing information to the patient and family caregivers, including family caregivers in EoL decision-making, and opting for death at home. Methods This cross-sectional study was performed as an online survey of 605 adults aged 50 or more in Israel, of which ~ 50% (n = 297) reported supporting a dying terminally ill relative in the last 3 years. Participants were requested to provide their account of the EoL process of their relative dying from a terminal illness in several aspects, as well as the EoL care practices utilized by them. Results The accounts of the 297 interviewees who supported a dying relative reveal a varied EoL typology. The utilization of end-of-life care practices was associated with the socio-normative beliefs of family caregivers but not with their socioeconomic status. Strong correlations were found between family caregiver support for three key practices (mechanical ventilation, artificial feeding, and family involvement in EoL) and the actual utilization of these practices in the care of dying patients. Conclusions The findings portray an important image of equity in the utilization of EoLCP in Israel, as the use of these practices was not associated with socioeconomic status. At the same time, the study found substantial diversity in family caregivers' preferences regarding EoL care practices use not related to socioeconomic status. We believe that differences in preferences that do not lead to problems with equity or other important societal values should be respected. Accordingly, policymakers and health system leaders should resist calls for legislation that would impose uniform EoL practices for all Israelis. Instead, they should take concrete steps to preserve and enhance the widespread current practice of practitioners to adapt EoL care to the varied needs and preferences of Israeli families and cultural, social, and religious subgroups. These steps should include providing frameworks and tools for family caregivers to support their loved ones close to their deaths, such as educational programs, seminars, supportive care before and during the end of life of their loved ones, etc.